2019
DOI: 10.3389/fpsyg.2018.02750
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Actual Strategic Behavior to Construct a Measure of Strategic Ability

Abstract: Strategic interactions have been studied extensively in the area of judgment and decision-making. However, so far no specific measure of a decision-maker's ability to be successful in strategic interactions has been proposed and tested. Our contribution is the development of a measure of strategic ability that borrows from both game theory and psychology. Such measure is aimed at providing an estimation of the likelihood of success in many social activities that involve strategic interaction among multiple dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 65 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, reciprocity requires a correct and exhaustive representation of the individual goals, incentives and potential actions of the interacting partners, as well as a full comprehension of the impact of one's choices on the counterpart. In this respect, extensive evidence in social decision making and behavioural economics has shown that these processes require specific cognitive abilities, including first-and second-order mentalizing and cognitive reflection [94][95][96][97][98][99]. These abilities emerge in preschool age [100] but develop and refine along childhood and early adolescence, around 6 and 12 years of age [101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reciprocity requires a correct and exhaustive representation of the individual goals, incentives and potential actions of the interacting partners, as well as a full comprehension of the impact of one's choices on the counterpart. In this respect, extensive evidence in social decision making and behavioural economics has shown that these processes require specific cognitive abilities, including first-and second-order mentalizing and cognitive reflection [94][95][96][97][98][99]. These abilities emerge in preschool age [100] but develop and refine along childhood and early adolescence, around 6 and 12 years of age [101][102][103].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reciprocity may require a correct and exhaustive representation of the individual goals, incentives and potential actions of the interacting partners, as well as a full comprehension of the impact of one's choices on the counterpart. In this respect, extensive evidence in social decision making and behavioral economics has shown that these processes require specific cognitive abilities, including first-and second-order mentalizing and cognitive reflection [80][81][82][83][84][85], which may be underdeveloped in childhood [86][87][88]. Moreover, in order to engage in reciprocal behavior, children should override selfish impulses in view of a long-term benefit in terms of affiliation and cooperation with peers, an ability that improve during childhood [89][90][91].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, competition is dynamically shaped through strategic interests and interactions within networks. Bilancini et al (2019) suggest competition often involves strategic interactions such as a strategic quotient test to determine abilities and rationality for strategic success. Strategic interactions are difficult to measure because it is a deviant form of behavior in that it takes place without organizational approval.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Strategic interactions are difficult to measure because it is a deviant form of behavior in that it takes place without organizational approval. Evidence provided by Bilancini et al (2019) collected data indicate success is dependent on understanding of others’ preferences and understanding of others’ cognitive skills. In addition, Thye et al (2011) found evidence for competitive networks that are structurally more cohesive tend to “promote group formation among self-interested actors who pursue those interests through dyadic exchanges” (p. 409).…”
Section: Theoretical Frameworkmentioning
confidence: 99%